2016
DOI: 10.4314/mcd.v11i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Which form of agreement works for communitybased management? A case study from southwestern Madagascar

Abstract: Aware that humans and nature are inseparably linked many organisations in Madagascar support the community-based natural resource management approach to promote the international policy of biodiversity conservation and protection. In this context, community associations have been introduced to transfer management and use rights for natural resources to the local population. However, the fast, donor-driven top-down procedure of establishing new rules contradicts the local rhythm and handling of rules. Against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
4
0
5
Order By: Relevance
“…Edmunds & Wollenberg, 2002). This is also supported by Thielsen's () observation that local decision‐making processes in the Mahafaly Plateau region are complex and take long time periods.…”
Section: Discussionsupporting
confidence: 56%
“…Edmunds & Wollenberg, 2002). This is also supported by Thielsen's () observation that local decision‐making processes in the Mahafaly Plateau region are complex and take long time periods.…”
Section: Discussionsupporting
confidence: 56%
“…La plupart des études comportant des détails sur les droits aux terres de pâturage se sont concentrées sur le plateau de Mahafaly (Moizo 2001 ;Goetter et Neudert 2016 ;Thielsen 2016), la région d'Atsimo Andrefana (Horning 2004) et la région du Menabe (Fauroux 2001, Scales 2011 Lorsque des pâturages considérés comme un bien commun sont convertis en terres agricoles, des conflits surgissent parfois entre éleveurs et agriculteurs. Cela a été le cas à Bevary, près de la réserve d'Ankarana dans le nord de Madagascar, où le fokonolona a autorisé un agriculteur à creuser un canal et à défricher un champ dans une partie où les pâturages sont gérés en commun (Gezon 1999).…”
Section: Les Terres De Pâturageunclassified
“…Il y a 20 à 30 ans, dans certaines régions du sud-ouest de Madagascar, les habitants ont commencé à réclamer la privatisation des droits en réponse à la pénurie d'arbres fourragers appelés « samatas » (Goetter et Neudert 2016 ;Thielsen 2016). L'encadré 3 décrit l'éventail des droits qui existent désormais pour les « samatas ».…”
Section: Les Terres De Pâturageunclassified
“…Local people's knowledge has been shown to provide important insights for sustainable land management and use of resources in south-western Madagascar [132]. Several authors have shown that to achieve effective conservation in Madagascar, every ethnic group should be integrated from the start [133,134]. More use should be made of existing forms of traditional, local agreements and institutions, because such local rules are generally more adhered to [133,135].…”
Section: Top 10 Knowledge Gapsmentioning
confidence: 99%